2018
DOI: 10.3390/w10111538
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Depletion in Planted Alfalfa Pastures in an Alpine Pastoral Area

Abstract: Alfalfa (Medicago sativa) has strong stress resistance, high nutritional value, good palatability for cattle, high yield and a drought tolerance mechanism, but long-term planting leads to soil desiccation. This research was carried out to examine the soil water conditions of alfalfa pastures with different planted ages, and determine the optimum time for alfalfa rotation in a plateau area of a sub-alpine monsoon climate. Soil water depletion, soil compaction and vegetation characteristics of alfalfa pastures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This interpretation is supported by Sun et al. (), in that increases in belowground alfalfa biomass with stand age (3.0, 4.2, and 4.5 kg m −2 at 2, 4, and 7 yr, respectively) followed increases in soil water extraction.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This interpretation is supported by Sun et al. (), in that increases in belowground alfalfa biomass with stand age (3.0, 4.2, and 4.5 kg m −2 at 2, 4, and 7 yr, respectively) followed increases in soil water extraction.…”
Section: Resultssupporting
confidence: 57%
“…These results confirm the direct relationship between alfalfa planting density (row spacing) and increased water extraction as indicative of high root activity in the soil profile. This interpretation is supported by Sun et al (2018), in that increases in belowground alfalfa biomass with stand age (3.0, 4.2, and 4.5 kg m −2 at 2, 4, and 7 yr, respectively) followed increases in soil water extraction.…”
Section: Root Weight Densitymentioning
confidence: 67%
“…In an alpine pastoral area in the Tibet Autonomous Region, Southwestern China, Sun et al [12] evaluated the processes of soil water depletion in planted alfalfa pastures. Alfalfa (Medicago sativa) has strong stress resistance, high nutritional value, good palatability for cattle, high yield, and a drought tolerance mechanism, but long-term planting leads to soil desiccation.…”
Section: Soil and Water Conservation In Croplandsmentioning
confidence: 99%
“…However, factors such as less rainfall, more runoff, high evaporation intensity, and excessive soil water depletion by vegetation of the deep soil moisture may result in a dried soil layer (Jipp et al 1998;Chen et al 2008;Wang et al 2018). Sun et al (2018) found that long-term cultivation of alfalfa pastures seriously consumed the deep soil water. This process of soil water deficit of alfalfa pastures was obviously aggravated after 4 years of planting.…”
Section: Introductionmentioning
confidence: 99%